Rapid qualitative profiling of metabolites present in Fusarium solani, a rhizospheric fungus derived from Senna spectabilis, using GC/MS and UPLC-QTOF/MSE techniques assisted by UNIFI information system - Vieira, Natália Carolina [UNESP] (2020)
Fungi are an important source of natural products found in a variety of plant species. A wide range of methods for the detection of metabolites present in fungi have been reported in the literature. The search for methodologies that allow the rapid detection of compounds present in crude extracts is crucial to enable the metabolite annotation doing a qualitative analysis of the complex matrix. Mass spectrometry is an important ally when it comes to in silico detection of previously reported metabolites. In this work, the ethyl acetate extract of Fusarium solani was analyzed by gas chromatography coupled to mass spectrometry (GC/MS) after derivatization process. The ethyl acetate extract was also investigated by liquid chromatography coupled with high-resolution tandem mass spectrometry assisted by the UNIFI software system. A library containing previously reported metabolites from the Fusarium genus was added to the UNIFI platform. Simultaneously, the extract was analyzed through anticholinesterase and antifungal assays. The analysis of the derivatized extract by GC/MS led to the putative identification of five metabolites, and the investigation using Ultra-High Performance Liquid Chromatography - Quadrupole Time-of-Flight Mass Spectrometry (UPLC-QTOF) analysis in data-independent acquisition mode (mass spectrometry) led to the annotation of 15 compounds present in the built-in Fusarium library added to the UNIFI system. The Fusarium solani extract showed potential anticholinesterase and in vitro antifungal activity supported by the detection of bioactive metabolites.